Analisis Fenomenologi Kepercayaan Zodiak Pada Mahasiswa Surabaya: Memahami Probabilitas Karakter dan Implikasinya terhadap Religiusitas - Galuh Aulia Mukti (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study examines how university students in Surabaya interpret zodiac horoscopes and how such beliefs impact their levels of religiosity. In the current era, the zodiac is no longer viewed merely as occult or mystical prophecy; instead, Generation Z largely understands it as a description of probabilities or tendencies regarding an individual's personality and psychology. Employing a descriptive qualitative method based on Husserl’s phenomenological approach, data were gathered through in-depth interviews with ten Surabaya students—comprising five Muslims, three Christians, one Catholic, and one Hindu. The findings reveal that the majority of students consume zodiac-related content via social media platforms such as TikTok and Instagram. They view the zodiac as a source of entertainment, a topic for social interaction, and a tool for self-reflection based on personality traits that resonate with their lives. However, despite the fact that their respective religions strictly forbid belief in fortune-telling, these students tend to compartmentalize their religious worship from the habit of reading horoscopes. They do not perceive believing in—or simply reading—horoscopes as a threat to their faith or religious observance. The study concludes that the prevalence of zodiac beliefs among university students represents a compromise between the search for self-identity in the digital age and a form of religious observance that is primarily formal and ritualistic.